Pengelolaan Taman Wisata Alam 17 Pulau Riung oleh BKSDA, Kabupaten Ngada NTT - Aurelius Basa Ndala Waka; I Nyoman Sukma Arida (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2022)
Nature Tourism Park 17 Riung Islands is administratively located in the Riung sub-district, NgadaRegency, NTT. This area has two types of ecosystems, namely land and water, making the Nature Tourism Park 17Riung Island be one of the tourist attractions worth a visitThis research was conducted to find out the management system carried out by BKSDA in managingNature Tourism Park 17 Riung Islands, the study used a qualitative data analysis. The method used in the form ofobservation, in-depth interviews and documentation studies.Overall, the management of Nature Tourism Park 17 Riung Island carried out by BKSDA has a system thathas been programmed, but there are some things that have not been maximized and require new information, forexample in the promotion section, cooperative relations with local governments, and the addition of tourismfacilities, and there is no specific division of labor.Keyword: Management, Method, profile of tourism.